MAIN ELEMENTS OF THE RULE OF LAW IN THE PRACTICE OF THE CONSTITUTIONAL COURT OF HUNGARY - Dr. Czine, Ágnes (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The rule of law is one of the most complex concepts in constitutional law, some principles of which permeate the entire functioning of the state, the relationship between the individual and the state. It is no coincidence that there have been many attempts to define the concept of the rule of law in the literature, legislation and international law as well, but we cannot speak of a uniform, universally accepted concept. The rule of law is strongly linked to the historical development of a given country. This article presents the problems encountered by the Constitutional Court of Hungary in its judgment and how it defined certain principles of the rule of law in practice. These decisions of the Constitutional Court affect the functioning of the state and legislation and are historically linked to the development after the change of regime in Hungary. There are different opinions in the literature that the Court used the concept of the rule of law formally, or as a subsidiary, or as an abstract, mysterious concept in different decisions. According to the position of the present article, no matter how the Constitutional Court approaches the concept, it is certain that the merits of the elaboration of the elements of this important constitutional institution and its application to Hungarian historical conditions are indisputable. In interpreting the concept of the rule of law, the Constitutional Court made it clear that the principle of the rule of law is not an auxiliary, secondary rule, and not merely a declaration, but an independent constitutional norm, the violation of which may in itself justify the unconstitutionality of a legal act.